A Rare Case of Splenic Artery Thrombosis Provoked By Medroxyprogesterone Acetate Requiring Splenectomy - Haider, Asad A; Bassi, Raghav; Prakash, Pranav; Hussein, Abdullahi; Alzghoul, Hamza; Bilal, Muhammad; Oyetoran, Anuoluwa; Iyer, Uma G (Curēus (Palo Alto, CA), 2023)
Splenic artery thrombosis is estimated to occur in only 0.016% of hospital admissions. Hormonal contraception is known to have hypercoagulable side effects, but splenic artery thrombosis (SAT) followed by functional autosplenectomy is a very rare side effect. We report a case of a 48-year-old female with persistent SAT provoked by depot medroxyprogesterone acetate (DMPA). She initially presented with severe left lower quadrant abdominal pain, and imaging revealed an extensive thrombus in the splenic artery. She was immediately started on intravenous heparin, and her symptoms improved after a few days, at which point she was discharged on oral apixaban. Three months after discharge, the patient presented with symptoms similar to the initial presentation. Further history revealed that she received an injectable DMPA shot prior to her initial admission. Other possible causes of SAT were ruled out. On imaging, her previous thrombus had increased in size and now filled the entire splenic artery. Therefore, the patient underwent robotic splenectomy with remarkable improvement in her symptoms. This case represents a rare clinical manifestation of a hypercoagulable state induced by DMPA. We review the existing literature to explain the epidemiology, presentation, diagnosis, and treatment of SAT, and incorporate our patient's presentation into the existing literature regarding the effect of contraception in inducing thrombotic events.